2016
DOI: 10.1097/md.0000000000005346
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polydeoxyribonucleotide prolotherapy on posterior tibial tendon dysfunction after ankle syndesmotic surgery

Abstract: Rationale:Ankle syndesmotic injuries occasionally require long-term therapy for recovery and can result in tendon injury. Posterior tibial tendon dysfunction (PTTD) is an acquired deformity that can cause flatfoot deformity. The current nonoperative management of PTTD includes nonsteroidal antiinflammatory drugs (NSAIDs), orthopedic devices. Although various treatment options have been attempted, optimal treatments for each stage of the condition are debated. Polydeoxyribonucleotide (PDRN) is effective in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Conversely, PDRN, whose action is derived from anti-inflammatory effects that promote wound healing by tissue regeneration, has no side effects. [ 15 , 16 ] PDRN repairs and regenerates the cellular damage by interacting with A2 purinergic receptor and stimulating the production of vascular endothelial growth factors. [ 15 ] PDRN had recently found a wide application in the medical field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, PDRN, whose action is derived from anti-inflammatory effects that promote wound healing by tissue regeneration, has no side effects. [ 15 , 16 ] PDRN repairs and regenerates the cellular damage by interacting with A2 purinergic receptor and stimulating the production of vascular endothelial growth factors. [ 15 ] PDRN had recently found a wide application in the medical field.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 , 16 ] PDRN repairs and regenerates the cellular damage by interacting with A2 purinergic receptor and stimulating the production of vascular endothelial growth factors. [ 15 ] PDRN had recently found a wide application in the medical field. Lim et al [ 15 ] reported the effectiveness of PDRN injection in posterior tibial tendon dysfunction patients undergoing ankle syndesmotic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, polydeoxyribonucleotide (PDRN) has begun to be used for neuropathic and musculoskeletal pain because of it its anti-inflammatory effects. [ 4 , 5 ] Although PDRN has not been studied for bone healing, it is known to promote wound healing through its collagen synthesis effects and by stimulating angiogenesis, unlike corticosteroids. [ 6 ] Moreover, PDRN is also known to have osteoblast-promoting properties, [ 7 ] and prevents cartilage loss.…”
Section: Introductionmentioning
confidence: 99%